Pemodelan karakteristik pengeringan pada proses pengeringan nanas (ananas comosus) - Nasution, Fachri Ibrahim; Rahman, Arief Fazlul; Laila, Widya; Nasirly, Riri; Arsi, Fadli (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The thin layer model describes the drying process uniformly, regardless of the control mechanism. Fundamentally, using experimental data on dried materials can be explained by the method used. The purpose of this research is to determine the characteristics of the pineapple drying process using a thin layer model. Drying using the oven method at 60°C. The thin layer drying model uses Newton, logarithmic, and Midilli models. The statistical parameters used are R2 and SSE. The water content obtained did not differ much between the two varieties, namely 13, 27, and 13.14 (% db). The results of the comparison of the three models used lead to different results with R² values ​​of 0.89–0.96 and SSE 0.0095–0.0013 based on the non-linear regression analysis used. The Midilli model shows the best results with R² parameters of 0.06 and 0.94 and SSE of 0.0019 and 0.0025..